1997
DOI: 10.1007/s002849900264
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Bacteriocin Production by Leuconostoc mesenteroides TA33a and Other Leuconostoc/Weissella Strains

Abstract: Leuconostoc (Lc.) mesenteroides TA33a produced three bacteriocins with different inhibitory activity spectra. Bacteriocins were purified by adsorption/desorption from producer cells and reverse phase high-performance liquid chromatography. Leucocin C-TA33a, a novel bacteriocin with a predicted molecular mass of 4598 Da, inhibited Listeria and other lactic acid bacteria (LAB). Leucocin B-TA33a has a predicted molecular mass of 3466 Da, with activity against Leuconostoc/Weissella (W.) strains, and appears simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 16 publications
1
42
1
Order By: Relevance
“…However, the contradiction between the calculated molecular mass according to the sequence and the mass spectrometry results (4597-4598 Da) revealed that more residues were missing (Papathanasopoulos et al 1997). Five years later, the complete amino acid sequence of mature LecC was determined, and its theoretical molecular weight (4596 Da) was closely consistent with the previous experimental value (Papathanasopoulos et al 1997;Fimland et al 2002b). Pediocin-like bacteriocins are translated as inactive precursors with Nterminal leader peptide mediating exportation of the bacteriocins ).…”
Section: Leucocin S (Previously Called Leuconocin S) Belongs To Classsupporting
confidence: 54%
See 1 more Smart Citation
“…However, the contradiction between the calculated molecular mass according to the sequence and the mass spectrometry results (4597-4598 Da) revealed that more residues were missing (Papathanasopoulos et al 1997). Five years later, the complete amino acid sequence of mature LecC was determined, and its theoretical molecular weight (4596 Da) was closely consistent with the previous experimental value (Papathanasopoulos et al 1997;Fimland et al 2002b). Pediocin-like bacteriocins are translated as inactive precursors with Nterminal leader peptide mediating exportation of the bacteriocins ).…”
Section: Leucocin S (Previously Called Leuconocin S) Belongs To Classsupporting
confidence: 54%
“…gelidum UAL187, have been reported to produce different class II bacteriocins, namely leucocin A (class IIa), leucocin B (class IId) and leucocin C (class IIa) van Belkum and Stiles 1995;Papathanasopoulos et al 1997). Ln.…”
mentioning
confidence: 99%
“…Bacteriocin activity assay. Bacteriocin activity was assayed using the agar well diffusion method, as described previously (Papathanasopoulos et al, 1997;.…”
Section: A P a P A T H A N A S O P O U L O S A N D Othersmentioning
confidence: 99%
“…Leucocins A-, B-and C-TA33a were purified by adsorption/desorption of bacteriocins from the producer cells of L. mesenteroides TA33a, followed by reversed-phase HPLC, as described previously (Papathanasopoulos et al, 1997;Yang et al, 1992). Aliquots of each purified preparation were lyophilized for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation